Pemanfaatan Barang Gadai Dalam Tinjauan Hadits Nabi Muhammad Saw - Satar, Muhammad (LPPM Sekolah Tinggi Ilmu Al-Qur'an Wali Songo Situbondo, 2023)
Islam in the development of fiqh muamalah recognizes the term pawn. Pawn is the transfer of the right of use owned as collateral for the loan they take. Of course this has been practiced in Islam since the time of the Prophet who later found various hadiths about pawning and its use. This study then aims to contain an in-depth explanation of how to use pawned goods as in the hadith of the Prophet Muhammad SAW. The research method used in this study is the library research method or literature study related to the hadith of the use of pawned goods. This study contains the hadith of how the pawn occurred and how the pawned goods were used in accordance with the hadith that became the basis and in this study contained the narrators of the hadith that were raised as well as criticisms of the sanad and the matan of the hadith. Keywords: Hadith, Pawn, Sanad, Matan